2016
DOI: 10.1159/000447950
|View full text |Cite
|
Sign up to set email alerts
|

What Are the Optimal Monitoring Techniques in Head and Neck Microvascular Reconstruction?

Abstract: Purpose: We evaluated the outcomes for widely used systems in terms of accuracy, salvage rates, and added cost compared to conventional monitoring. Methods: We performed a narrative review of the literature (high-impact report). Results: The overall free flap success for head and neck reconstruction is at least 95% using any type of monitoring. Salvage rates in decreasing frequency of monitoring techniques are 85% with near-infrared spectroscopy (NIRS), 81% with implantable Doppler, and 61.5% with conventional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…There have been many criteria used for classification of monitoring methods. Moubayed 18 for example made two classes namely; (a) widely used -DVM and Doppler, near-infrared spectroscopy and (b) experimental -all other methods. Schoeller 19 chose objectivity of the method as the criteria and concluded that his two classes were; (a) subjective -DVM and (b) objective -all the other methods.…”
Section: Methods Of Monitoring the Micro-vascular Flapmentioning
confidence: 99%
See 4 more Smart Citations
“…There have been many criteria used for classification of monitoring methods. Moubayed 18 for example made two classes namely; (a) widely used -DVM and Doppler, near-infrared spectroscopy and (b) experimental -all other methods. Schoeller 19 chose objectivity of the method as the criteria and concluded that his two classes were; (a) subjective -DVM and (b) objective -all the other methods.…”
Section: Methods Of Monitoring the Micro-vascular Flapmentioning
confidence: 99%
“…An ideal monitoring technique therefore should be easy to apply, objective, continuous, non-invasive, safe, inexpensive, easily and validly interpreted by medical and nursing staff and cost-effective 18,42,177 . More than 40 monitoring methods have been reported over a 45-year period of using MF's, the first of course being DVM.…”
Section: The Ideal Monitoring Methodsmentioning
confidence: 99%
See 3 more Smart Citations